A teljesítményértékelés és a mentorálás szerepe egy gyakornoki programban = The role of performance evaluation and mentoring in a trainee program - Szondi Réka (Taylor : gazdálkodás- és szervezéstudományi folyóirat, 2018)
The success of companies will be determined by the resupply of experts. Employers increasingly demand application-oriented knowledge, and the usability of knowledge generally requires the combination and integration of knowledge from various disciplines (Árváné et al. 2016). Nowadays, finding and keeping the talented employees are key factors. The research analyzes a trainee program of a large company. The program was recommended to entrants of the labour market or those who have 1-1,5 years of work experience. The main objective is the evaluation of the effectiveness of the program through some of the HR functions. This study contains the performance evaluation and the role of the mentoring. From the induction into the organization, the technical mentor gives assistance to the trainees. One of the main elements of the performance is the feedback. the trainees have to write a weekly report, and after that, the mentor gives them a personalized review based on their performance. The questionnaire was edited for the trainees at the company, and they were asked about their future plans and their intentions about staying at the company after the program too. The questionnaire was analyzed with IBM SPSS Statistics 23.0 statistical software. The used methods are descriptive statistics, correlation, and Chi-square tests. In the course of the research, an interview was done with the technical mentor, which was based on the questionnaire. In point of the results, recommendations were defined connected to the assumed shortages of the program, also to increase the efficiency of operation. In conclusion, the maintenance of the trainee program is equally beneficial for the trainees and for the company as well.